2013
DOI: 10.1371/journal.pone.0063743
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Anxiety Scores in First and Repeat IVF Cycles: A Pilot Study

Abstract: BackgroundThe role of stress in reproduction, particularly during treatment for infertility, has been of considerable interest; however, few studies have objectively measured stress and anxiety over the course of the IVF cycle or compared the experience of first-time and repeat patients.MethodsThis prospective cohort pilot study enrolled 44 women undergoing IVF at a university-based clinic to complete the State-Trait Anxiety Inventory (STAI), Perceived Stress Scale (PSS) and Infertility Self-Efficacy Scale (IS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 40 publications
3
89
1
Order By: Relevance
“…The mean anxiety score for women was higher at the time of the β-HCG dosage (the pregnancy test) than at pretreatment (ZAS, m = 32.64 vs. 31.95) [9]. No differences in anxiety level were detected between women who had received the first cycle and those who had undergone a repeated cycle of IVF treatment [30].…”
Section: Anxietymentioning
confidence: 85%
See 2 more Smart Citations
“…The mean anxiety score for women was higher at the time of the β-HCG dosage (the pregnancy test) than at pretreatment (ZAS, m = 32.64 vs. 31.95) [9]. No differences in anxiety level were detected between women who had received the first cycle and those who had undergone a repeated cycle of IVF treatment [30].…”
Section: Anxietymentioning
confidence: 85%
“…Women and/or men's anxiety was explored in ten studies using different instruments: STAI [28][29][30], the Zung Anxiety Scale (ZAS) [9,26], MAACL [10,31], SAS [27,32], and PRIME-MD [17]. The incidence of anxiety in women was high on the day of the oocyte retrieval (ZAS ≥ 40, 33.3 %; PRIME-MD, anxiety disorder: 14.8 %) [17,26], within 2 h after the embryo transfer (SAS 40, 38.5 %) [27], and 20 days after the embryo transfer (SAS > 40, 25.9 %) [32].…”
Section: Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…In a pilot study on a group of 44 women, an increased level of anxiety in the psychometric scales was found in women undergoing IVF treatment during the whole course of therapy [14]. It was also found that women initially who had a lower level of anxiety before the oocyte retrieval, had a higher pregnancy rate [14].…”
Section: The Influence Of Anxiety On the Effects Of Infertility Treatmentioning
confidence: 97%
“…It seems however that stress related to infertility can negatively affect the outcomes of infertility treatment. Infertile women seem to be more affected by stress compared to their male partners [10][11][12][13][14], which may be due to their direct involvement in invasive ART procedures. In our work we present a review of current literature on anxiety and depressive disorders in women undergoing infertility treatment, including the influence of anxiety and depression on infertility treatment outcome and the effect of ART procedures on the risk of anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%